2012
DOI: 10.5535/arm.2012.36.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia due to Retropharyngeal Abscess that Incidentally Detected in Subarachnoid Hemorrhage Patient

Abstract: Cerebral hemorrhage is one of the most common causes of dysphagia. In many cases, dysphagia gets better once the acute phase has passed. Structural lesions such as thyromegaly, cervical hyperostosis, congenital web, Zenker's diverticulum, neoplasm, radiation fibrosis, and retropharyngeal abscess must be considered as other causes of dysphagia as well. Retropharyngeal abscess seldom occur in adults and if it does so, a search for a prior dental procedure, trauma, head and neck infection is needed. The symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is reported that SAH accounts for approximately 15% of cerebrovascular diseases ( 2 ). If there is no effective clinical treatment in the early stages of bleeding, approximately 13% patients will die suddenly ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that SAH accounts for approximately 15% of cerebrovascular diseases ( 2 ). If there is no effective clinical treatment in the early stages of bleeding, approximately 13% patients will die suddenly ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…환에서의 연하장애 유병률에 대한 연구는 부족하고 주로 증례보고가 대부분이지만[6][7][8][9], 연하와 관련 있는 신경 및 근육 등의 해부학적 손상이 있을 경우 연하장애가 발생할 수 있음 을 추정할 수 있다. 구인두 연하장애의 치료는 크게 보존적 치료와 침습적 치료 로 나눌 수 있다.…”
unclassified